2012
DOI: 10.5194/acp-12-10649-2012
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft-based observations and high-resolution simulations of an Icelandic dust storm

Abstract: Abstract. The first aircraft-based observations of an Icelandic dust storm are presented. The measurements were carried out over the ocean near Iceland's south coast in February 2007. This dust event occurred in conjunction with an easterly barrier jet of more than 30 m s −1 . The aircraft measurements show high particle mass mixing ratios in an area of low wind speeds in the wake of Iceland near the coast, decreasing abruptly towards the jet. Simulations from the Weather Research and Forecasting Model coupled… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…[] used the Lagrangian particle dispersion model FLEXPART [ Stohl et al ., ] to model the quantity and dispersion of dust generated from within the Arctic region. FLEXPART has been widely used to provide insight into particle dispersion patterns worldwide and has been applied at high latitudes to individual dust events [ Blechschmidt et al ., ] and the resuspension of volcanic ash [ Thorsteinsson et al ., ] in Iceland. Groot Zwaaftink et al .…”
Section: Regional and Global Dust Emissions From High Latitudesmentioning
confidence: 83%
See 1 more Smart Citation
“…[] used the Lagrangian particle dispersion model FLEXPART [ Stohl et al ., ] to model the quantity and dispersion of dust generated from within the Arctic region. FLEXPART has been widely used to provide insight into particle dispersion patterns worldwide and has been applied at high latitudes to individual dust events [ Blechschmidt et al ., ] and the resuspension of volcanic ash [ Thorsteinsson et al ., ] in Iceland. Groot Zwaaftink et al .…”
Section: Regional and Global Dust Emissions From High Latitudesmentioning
confidence: 83%
“…[2016] used the Lagrangian particle dispersion model FLEXPART [Stohl et al, 1998] to model the quantity and dispersion of dust generated from within the Arctic region. FLEXPART has been widely used to provide insight into particle dispersion patterns worldwide and has been applied at high latitudes to individual dust events [Blechschmidt et al, 2012] [Thorsteinsson et al, 2012] in Iceland. Groot Zwaaftink et al [2016] suggest that from 2010 to 2012 dust emissions from land north of 60°N accounted for 1.7-5.3% of global dust emissions (averaging 48 Tg yr À1 ).…”
Section: Regional and Global Dust Emissions From High Latitudesmentioning
confidence: 99%
“…Here we suggest several possibilities: Local effects . Orography can strongly perturb both the velocity and direction of surface winds at a local scale; this orographic influence has been invoked to explain spatial patterns of elevated and suppressed particle flux during previous resuspension events in southern Iceland [ Olafsson , ; Blechschmidt et al ., ]. A documented ash storm in Kirkubaerklaustar on the morning of 6 March [ Morgunblaðið , ] provides key evidence that significant material from the Grímsvötn source region was already in suspension.…”
Section: Discussionmentioning
confidence: 99%
“…However, dust emissions from the Arctic and Antarctic have received increased attention (Arnalds, 2010;Bullard, 2013;Gillies et al, 2013;Muhs et al, 2013). Research shows frequent dust storms in South Iceland moving into the North Atlantic Ocean (Arnalds and Metúsalemsson, 2004; and into the Arctic from Northeast Iceland (Dagsson-Waldhauserova et al, 2013a), and it has been suggested that Iceland is among the world's most active dust sources (Arnalds, 2010;Blechschmidt et al, 2012;Bullard, 2013).…”
Section: Introductionmentioning
confidence: 99%